IMPLEMENTASI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK TERHADAP PELANGGARAN LALU LINTAS YANG DILAKUKAN OLEH ANAK - Bastian, Herly; Rosmely, Wirna (UNES Journal of Swara Justisia, 2017)
This study examines the Implementation of UU No. 11 Tahun 2012 on the Criminal Justice System of Children against traffic violations committed by the Child. This is motivated by the process of settling cases of traffic violations committed by the Child ranging from the level of investigator to trial in court is not based on UU No. 11 Tahun 2012, so that contrary to the principle of the Criminal Justice System of the Child such as not paying the best interest for the Child, The right of the Child to deal with the law. This study uses secondary data as the main data obtained from literature / document studies supported primary data in the form of interviews. Based on the result of the research, it is found that Implementation of UU No. 11 Tahun 2012 on traffic violations conducted by children has not been applied maximally, not yet apply the concept of restorative justice so that contrary to the principles of the Criminal Justice System Law of Children does not give priority to the best interests for the Children. Second, the obstacles faced in the implementation of UU No. 11 Tahun 2012 on the Criminal Justice System for Child Trafficking violations committed by the Child is caused by several factors, including: Disharmony UU No. 11 Tahun 2012 on Child Criminal Justice System with UU No. 22 Tahun 2009 on Road Traffic and Transportation, Lack of Implementing UU No. 11 Tahun 2012 on Child Criminal Justice System, Regulation of UU No. 22 Year 2009 on Traffic and Road Transport that is not appropriate with the current situation, Knowledge and Law enforcement mindset.